Gaps in Marketing: Challenges for Business Education in the West African Senior Secondary School Commerce Curriculum - Isaac Oladepo & Sodipo Olufunlayo Olayinka, Onigbinde (British Journal of Marketing Studies, 2017)
This study evaluated the concepts of commerce and marketing, the bases of, and dynamic phases of marketing and advanced rationale for integrating additional contents of marketing in the West African senior secondary school commerce curriculum. Topical elements in the existing West African senior secondary school commerce curriculum were identified for the proposed integration as a way of renewal of the curriculum to meet new challenges facing the learners in the emerging business economy of West Africa. Hence in the light of the existing relationship between commerce and marketing and the changes in the relatively new business worlds, it has become imperative to inject some additional contents of marketing into the existing commerce curriculum in the West African Senior Secondary Schools (WASSS). However, marketing as a discipline is needed to be accorded the right recognition and approved as a stand-alone subject in the West African Senior School Certificate Examination (WASSCE).